PsycEXTRA Dataset 2014
DOI: 10.1037/e508812015-001
|View full text |Cite
|
Sign up to set email alerts
|

What we Know about Youth Employment: Research Summary and Best Practices

Abstract: The goal of this white paper is to bring greater attention to the issue of youth employment, and, through reviewing research, identify ways that current practice can be enhanced. We accomplish this objective by highlighting why youth employment demands more focused attention, outlining the key research findings, reporting on international similarities as well as differences, and sharing a list of best practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…As prospects for a career are limited during harsh conditions, being less preoccupied and less directive with planning one's career directions and being more open and flexible may increase the sense of employability as it may widen job options and increase and perceive chances of gaining employment. This notion arises because studies have found that individuals who utilize a combination of engagement (such as career-enhancing strategies) and disengagement strategies (such as career passivity) tend to cope better with persistent futile job searches and prolonged unemployment (Lin & Leung, 2010;Searle et al, 2014). In the same line of reasoning, passivity or career disengagement had been considered as an adaptive way of coping with unemployment, reducing detrimental effects of occupational uncertainty and preventing mental health when labor market conditions are negative (Tomasik et al, 2010;Korner et al, 2012).…”
Section: Personal Resources and Harsh Labor Conditionsmentioning
confidence: 99%
“…As prospects for a career are limited during harsh conditions, being less preoccupied and less directive with planning one's career directions and being more open and flexible may increase the sense of employability as it may widen job options and increase and perceive chances of gaining employment. This notion arises because studies have found that individuals who utilize a combination of engagement (such as career-enhancing strategies) and disengagement strategies (such as career passivity) tend to cope better with persistent futile job searches and prolonged unemployment (Lin & Leung, 2010;Searle et al, 2014). In the same line of reasoning, passivity or career disengagement had been considered as an adaptive way of coping with unemployment, reducing detrimental effects of occupational uncertainty and preventing mental health when labor market conditions are negative (Tomasik et al, 2010;Korner et al, 2012).…”
Section: Personal Resources and Harsh Labor Conditionsmentioning
confidence: 99%
“…We were able to observe the added stress that joblessness creates, not only for young people themselves but, also for their families and, through that, into their communities and society as a whole. These issues are clearly highlighted in our Society of Industrial and Organizational Psychology (SIOP) youth employment white paper (Searle, Erdogan, Peiró & Klehe, 2014). In that paper, we discuss how youth unemployment is a global phenomenon that is adversely affecting young people across the world for a variety of reasons.…”
Section: Why Is Youth Employment Important For Eawopii?mentioning
confidence: 99%